Intra-Observer Variation of Space Available in the Mandibular Dental Arch by Two Different Measuring Tools-Vernier Calliper and Brass Wire with a Millimetre Ruler - Shahid, Rooma; Jan, Abdullah; Fazal, Ayesha; Mughal, Alaina Tariq; Ghaffar, Fareena; Mehmood, Sundas (Pakistan Armed Forces Medical Journal, 2023)
Objective: To check the variation of space available in the mandibular dental arch using different tools, i.e., Vernier caliper and brass wire with a millimeter ruler.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Orthodontics, Armed Forces Institute of Dentistry (AFID), Rawalpindi Pakistan, from Sep to Dec 2019.Methodology: Seventy-five dental casts of patients, with an age range between 12-25 years were included in the study. The variation of the space available using two different measuring tools (Vernier calliper and brass wire with millimetre ruler) in the mandibular arch was determined by the same observer to assess random and systematic errors. The examiner recorded the measurements, and then the same examiner repeated the measurements after ten days by taking two readings each using the blinding technique to minimize bias. Random and systematic errors were analyzed with the use of two methods.Results: Systematic errors were found to be significant with brass wire with millimetre ruler method only (p-value=0.02). For random errors, the Vernier calliper can be considered a better method to measure reproducibility and repeatability. However, brass wire with a millimetre ruler method can be considered better for measuring repeatability than reproducibility since the value to measure random errors was less than 1mm but in the upper limits (p-value=0.091).Conclusion: In the current study, it is concluded that the Vernier calliper is more precise in measuring the readings in orthodontics for arch space measurement than that of brass wire with a millimetre ruler. However, brass wire